2010
DOI: 10.1186/1546-0096-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Review for the generalist: evaluation of low back pain in children and adolescents

Abstract: Back pain is common in children and adolescents. Most cases of back pain are non-specific and self-limiting. In children and adolescents, pain is usually related to the posterior elements of the spine and disc-related problems are rare. Serious pathology, including malignancy and infection needs to be excluded. Evaluation and management is challenging and requires a thorough history and physical exam, and understanding of the immature skeleton. Diagnostic imaging is useful in the evaluation of a child or adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 27 publications
2
42
1
4
Order By: Relevance
“…However, these results are consistent with the results of King et al review study, which was conducted to determine the prevalence of pain in children and adolescents and reported a prevalence rate of 14% to 24% (28). LBP is one of the significant problems of adolescents and should be prevented (29). Steffens et al showed in their review study that exercise could prevent LBP, but back belts and shoe insoles did not affect LBP reduction (30).…”
Section: Discussionsupporting
confidence: 83%
“…However, these results are consistent with the results of King et al review study, which was conducted to determine the prevalence of pain in children and adolescents and reported a prevalence rate of 14% to 24% (28). LBP is one of the significant problems of adolescents and should be prevented (29). Steffens et al showed in their review study that exercise could prevent LBP, but back belts and shoe insoles did not affect LBP reduction (30).…”
Section: Discussionsupporting
confidence: 83%
“…Any area highlighted as abnormal by pGALS should be examined in more detail using paediatric regional examination of the musculoskeletal system (pREMS) [31]. Several review articles provide detailed explanation of examination of the back [32], hip [33], knee [34], foot and ankle [35]. Further practical guides are available on the Paediatric Musculoskeletal Matters website [36].…”
Section: Msk Examination In Childrenmentioning
confidence: 99%
“…There is evidence that supports the use of exercise as a therapeutic tool to improve flexibility 3 . Considering the high rates of back pain among adolescents (10-59%) 6,7 and the poor flexibility values observed among school aged children 5,8 this has influenced the offering of flexibility programs during school hours among school aged children.…”
Section: Introductionmentioning
confidence: 99%